Extensive Reading And Dictionaries An Approach To vocabulary acquisition To meet contextual requirements For Advanced English Language Learners - Fitri Rizki; Jalaluddin Jalaluddin (Aksara: Jurnal Bahasa dan Sastra, 2018)
Fully understanding the message delivered in written English or Spoken English will save a lot of time for the readers as well as the lisnters to have the comprehension of  the information conveyed..The use of appropriate words that  represent what the writer or the speaker has in his mind has  the potential to enable the readers or the listeners to take the required messages in the shortest possible time. With  representivve  vocabulary that are used to meet  contextual requirements will guarantee a message to reach its required object. Correct use of words will create fully meaningful messages to their readers as well as listeners. By extensive reading and use of monolingual dictionaries, a learner will gain the  vocabulary acquisition. DOI: http://dx.doi.org/10.23960/aksara/v19i2.pp114-126